Dérision de l’étranger et exaltation du Britannique dans l’œuvre de William Hogarth 1697-1764 - Isabelle Baudino (Revue LISA)
As a “comic history painter” William Hogarth frequently mocked his contemporaries and was much famed for his works in which he satirised the mores of his time. Yet even if he ridiculed his British compatriots, he developed a complex graphic rhetoric to make fun of foreigners. Among them, both the French and the Italians were particular butts for ridicule and this can be explained by the wars as well as by the more pervasive conflict which opposed Britain to the Continent throughout the eighteenth century. Indeed the prolonged warfare with France may account for the openly patriotic contents of certain compositions. There also existed a euphemised version of these armed conflicts, which affected most the emerging British artistic field, namely the cultural war in which Hogarth took an active and creative part. He elaborated visual stereotypes in which derision was the basis for the differentiation and exclusion of foreigners, of foreign influence on political, religious, moral or cultural matters. The other side of the visual derision of foreigners was the exaltation of Britishness since the painter encouraged his British viewers to define themselves collectively against foreigners as they imagined them to be, hence contributing to the forging of the British national identity.